„Erotodidactica meretricum”. Szkoła kurtyzan w komedii łacińskiej od Plauta i Terencjusza po XVII wiek - Rzepkowski, Krzysztof (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
The paper presents the so-called courtesan school as one of the most attractive literary topoi in Latin comedy from the palliata in Antiquity, through elegiac comedy in the Middle Ages, to humanist comedy in the Renaissance and the Terentius Christianus of Cornelius Schonaeus Goudanus.

In the third act of Plautus’ Asinaria an old procuress named Cleareta rebukes her daughter Philaenium, a young prostitute, for excessive sentimentality and reproaches her for turning away wealthy clients. At the beginning of Terence’s Hecyra grey-haired Syra instructs young courtesan Philothis “to take pity upon no one, but plunder, fleece, and rend every man she lays hold of”. In De cerdone, an anonymous twelfth-century elegiac comedy, an aged procuress encourages the young beautiful wife of a tailor to be unfaithful to her ugly husband and to arrange a sexual appointment with an aged but very rich priest. In Ugolino Pisani’s Philogenia et Epiphebus, a fifteenth-century comedy, two procuresses, Servia and Irtia, teach each other how to treat their clients. The words of one of them – cum aurum accipimus, tum gratiam habeamus – constitute the motto for all procuresses and aged courtesans in Latin comedy: from the palliata in Antiquity, throughout elegiac comedy in the Middle Ages, till humanist comedy in the Renaissance and Terentius Christianus of Cornelius Schonaeus Goudanus the so-called courtesan school is one of the most attractive literary topoi. How is it introduced to the stage by classical authors? How do Renaissance and reformation authors revive it? And finally, does it fulfil the didactic purpose of comedy? These are the questions I investigate in this paper.
Erotodidactica meretricum. Courtesan School in the Roman Comedy
Keywords: comedy; palliata; lena; courtesan; meretrix